Floral development in Gomphrenoideae (Amaranthaceae) with a focus on androecial tube and appendages. (13th June 2019) - Sánchez-Del Pino, Ivonne; Vrijdaghs, Alexander; De Block, Petra; Flores-Olvera, Hilda; Smets, Erik; Eliasson, Uno
Abstract: The gomphrenoid group of Amaranthaceae ('Gomphrenoideae') comprises the alternantheroid, iresinoid and gomphrenoid subclades. Using scanning electron and light microscopy, we studied flowers of seven genera representing all three subclades with a focus on the androecial tube, which is present in all Gomphrenoideae, and on which the stamens are inserted. Two kinds of appendages, either on the androecial tube or on the filaments, are observed in most Gomphrenoideae. The main aim of this paper is to determine the nature of these appendages. In the alternantheroid and iresinoid subclades, appendages on the androecial tube often occur, originating from primordia on its rim. In the gomphrenoid subclade, similar appendages on the androecial tube only occur in Pseudoplantago, but several genera have appendages originating from the bases of the filaments; they are therefore called appendages on the filaments. The two kinds of appendages are mutually exclusive. We consider them to be non-homologous, de novo organs, constituting different characters, each with a set of character states. The floral ontogeny of the taxa studied concurs with earlier findings in Amaranthaceae. An early dome-shaped receptacle was observed in Gomphrenoideae and in Amaranthus (Amaranthoideae). A central ovule primordium develops independently from an annular ovary wall but later is transiently attached to it, suggesting that this (ontogenetically) acarpellate ovary evolved from an ovary with a carpellary organization. Anatomical evidence for a perigynous hypanthium in Guilleminea is given for the first time. In Gomphrenoideae, flowers are usually bisexual, but functionally male flowers occur in Iresine . Our results show that in Amaranthus floral sexuality is more flexible than generally accepted.